Energia da biomassa de cana-de-açúcar sob influência de hidrogel e cobertura vegetal em dois sistemas de plantio - Pinto, Luis Eduardo Vieira (2011)
Aiming to evaluate the interaction of hydrogel polymer and vegetation cover, in two planting systems (groove and windrow), the possible interference of the energy value of sugar cane biomass, at four dosages were used (0.0, 26.67, 53.33 and 80.00 kg of polymer per hectare) and four treatments with dry matter ratoon sugar cane, installed at the harvest of first cut in June 2009, and the concentrations (without leaves, in dose 0), dry leaves, at 5 t dry matter ha-1; green leaves at 10 t dry matter ha-1, and mixture of green leaves and dry leaves at 15 t dry matter ha-1. The experimental unit (plot) consisted of five rows with five meters long, with now spacing of 1.5 m (area of 37.5 m2). The experiment was located on the campus of UNOESTE II, and the soil was characterized as Sandy Red Yellow Distroferric, typical A moderate, middle-clay texture (Embrapa, 1999). The climate in the region is classified as Aw, with summer rainy season and dry season in winter. The cultivar used was RB 86 7515 planted in December 2007 and harvested in June 2009 (18 months), and the ratoon of this cultivar was used in this study. The experimental design was a factorial split plot (2x4), with two planting systems used in 2007 at crop installation process, with four doses of hydrogel polymer and four treatments with mulching. Evaluations were made regarding the calorific power of sugar cane during the months of August, September and October 2010, in addition to biomass productivity, levels of ATR and fiber of sugar cane for the month of August and top calorific power of straw in October 2010. All data were subjected to analysis of variance (ANOVA, p <0.05) and the means were compared by Scott-Knott (p <0.05) according to Gomes (1990). For the construction of graphs and statistical regressions the mathematical program Microcal Origin 6.0 was used. The results obtained show that planting systems not Groove terraces and promoted differences between themselves, when compared to the variables analyzed not experiment. The use of polymer the dose of 53,33 k ha-1 provided a higher biomass and bioenergy system per hectare.